2019
DOI: 10.14440/bladder.2019.789
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic P2X7 receptors as therapeutic targets in interstitial cystitis/bladder pain syndrome; key role of ATP signaling in inflammation

Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic lower urinary tract condition. Patients with IC/BPS suffer from debilitating pain and urinary urgency. The underlying etiology of IC/BPS is unknown and as such current treatments are mostly symptomatic with no real cure. Many theories have been proposed to describe the etiology of IC/BPS, but this review focuses on the role of inflammation. In IC/BPS patients, the permeability of the urothelium barrier is compromised and inflammatory cells infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 148 publications
(212 reference statements)
0
14
0
Order By: Relevance
“…The P2X7 receptors have recently been hypothesized to be involved in bladder cystitis including IC/BPS (Taidi et al, 2019) due to their important role in inflammation (De Marchi et al, 2016). It is suggested that, under pathophysiological conditions, a higher concentration of extracellular ATP (Sun and Chai, 2006) causes prolonged activation of the P2X7 receptor, resulting in extreme permeability of the cell membrane to ions (Hattori and Gouaux, 2012) and formation of a large membrane pore.…”
Section: Introductionmentioning
confidence: 99%
“…The P2X7 receptors have recently been hypothesized to be involved in bladder cystitis including IC/BPS (Taidi et al, 2019) due to their important role in inflammation (De Marchi et al, 2016). It is suggested that, under pathophysiological conditions, a higher concentration of extracellular ATP (Sun and Chai, 2006) causes prolonged activation of the P2X7 receptor, resulting in extreme permeability of the cell membrane to ions (Hattori and Gouaux, 2012) and formation of a large membrane pore.…”
Section: Introductionmentioning
confidence: 99%
“…We used the same concentration of LX as that in the mouse model (4.5 mM, 100 μm) [ 4 ], but we increased the volume of LX (4.5 mM, 200 μm) in the current study after considering the bladder volume of rats [ 30 ]. A potential strength of this study is the use of a TLR7-induced Hunner-type IC rat model system compared with other commonly used IC/BPS model systems induced with cyclophosphamide [ 31 , 32 ], lipopolysaccharide [ 33 ], hydrochloric acid (HCl) [ 7 , 13 ], uroplakin [ 14 , 29 ] and ketamine [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cystoscopy, IC/BPS is diagnosed when the bladder has been filled to its maximum capacity (at a pressure of 80–100 cm H 2 O). In IC/BPS patients, mucosal splitting, glomerulations, and Hunner ulcers are frequently observed mucosal damage in IC/BPS [ 101 ]. In order to diagnosis of the HIC/BPS or NHIC/BPS, cystoscopy is recommended to examine the bladder mucosa after bladder filling and determine the presence or absence of Hunner lesions [ 102 , 103 ].…”
Section: Clinical Diagnosis For Ic/bpsmentioning
confidence: 99%
“…ATP is released from urothelium in response to bladder stretch and could act on urothelial purinergic receptors. Patients with IC/BPS have increased afferent nerve density and ATP release, which might affect the symptoms of pain, urgency and frequency [ 101 ]. The expression of both P2X and P2Y receptors in nerve fibers and myofibroblasts, located close to urothelium and detrusor muscle, and the sensitivity of these receptors to ATP suggest that ATP release may influence function of myofibroblasts and afferent nerve endings [ 158 ].…”
Section: Current Investigated Biomarkers In Ic/bpsmentioning
confidence: 99%
See 1 more Smart Citation